CD8+PD-1+ to CD4+PD-1+ ratio (PERLS) is associated with prognosis of patients with advanced NSCLC treated with PD-(L)1 blockers. Issue 2 (7th February 2022) - Duchemann, Boris; Naigeon, Marie; Auclin, Edouard; Ferrara, Roberto; Cassard, Lydie; Jouniaux, Jean-Mehdi; Boselli, Lisa; Grivel, Jonathan; Desnoyer, Aude; Danlos, François-Xavier; Mezquita, Laura; Caramella, Caroline; et al.
Abstract : Background: Programmed cell death protein-1 (PD-1) expression has been associated with activation and exhaustion of both the CD4 and CD8 populations in advanced non-small cell lung cancer (aNSCLC). Nevertheless, the impact of the balance between circulating CD8 + PD-1 + and CD4 + PD-1 + in patients treated with immune checkpoint blockers (ICB) is unknown. Methods: The CD8 + PD-1 + to CD4 + PD-1 + ratio (PD-1-Expressing Ratio on Lymphocytes in a Systemic blood sample, or 'PERLS') was determined by cytometry in fresh whole blood from patients with aNSCLC before treatment with single-agent ICB targeting PD-1 or programmed cell death-ligand 1 (PD-L1 (discovery cohort). A PERLS cut-off was identified by log-rank maximization. Patients treated with ICB (validation cohort) or polychemotherapy (control cohort) were classified as PERLS+/− (above/below cut-off). Circulating immune cell phenotype and function were correlated with PERLS. A composite score (good, intermediate and poor) was determined using the combination of PERLS and senescent immune phenotype as previously described in aNSCLC. Results: In the discovery cohort (N=75), the PERLS cut-off was 1.91, and 11% of patients were PERLS+. PERLS + correlated significantly with median progression-free survival (PFS) of 9.63 months (95% CI 7.82 to not reached (NR)) versus 2.69 months (95% CI 1.81 to 5.52; p=0.03). In an independent validation cohort (N=36), median PFS was NR (95% CI 7.9 to NR) versus 2.00 months (95% CI 1.3 to 4.5; p=0.04) for PERLS + and PERLS−, respectively; overall survival (OS) followed a similar but non-significant trend. In the pooled cohort (N=111), PERLS + correlated significantly with PFS and OS. PERLS did not correlate with outcome in the polychemotherapy cohort. PERLS did not correlate with clinical characteristics but was significantly associated with baseline circulating naïve CD4 + T cells and the increase of memory T cells post-ICB treatment. Accumulation of memory T cells during treatment was linked to CD4 + T cell polyfunctionality. The composite score was evaluated in the pooled cohort (N=68). The median OS for good, intermediate and poor composite scores was NR (95% CI NR to NR), 8.54 months (95% CI 4.96 to NR) and 2.42 months (95% CI 1.97 to 15.5; p=0.001), respectively. The median PFS was 12.60 months (95% CI 9.63 to NR), 2.58 months (95% CI 1.74 to 7.29) and 1.76 months (95% CI 1.31 to 4.57; p<0.0001), respectively. Conclusions: Elevated PERLS, determined from a blood sample before immunotherapy, was correlated with benefit from PD-(L)1 blockers in aNSCLC.